Postural sway control as a derivative of core muscles training among adolecent archers - Pathmanathan K. Suppiah
The objective of this study was to investigate the effectiveness of a core stability training program in reducing the postural sway :lITIOng adolescent archers. Expert athletes in archery are able to rapidly achieve postural stability compared to beginners and novice athletes. The core region of the body is where the center of gravity for humans is located and where all human movement begins. Participants of this study were adolescent archers aged between 13 - 18 years. Employing a mixed time series design, the participants (n= J 2) were divided in two groups. The experimental group underwent a supplementary core stability training programme in tandem with their regular training programme. The control group underwent their regular training programme only. The training program programme was eight weeks long with data collected at three timepoints pre training; post four weeks training and post eight weeks. Postural sway was measured on the antero-posterior plane and medic lateral plane. Mixed factorial ANOV A yielded significant interactions over time in the performance of the push up; plank; archery performance and postural sway. There were also significant differences in the performances of all fitness components and archery. Postural sway between the experimental and control group was significantly di.fferent on both planes at T:~: (CoP range x - F( 1, I 0) = 7.952, P <.05, d = 1.302; CoP range y - T2; F(I,IO) = 7 .. 887, p <.05). The results were replicated at T3; CoP range x > F(L,lO)= 7.952, p <.05; CoP range y - F(l,10)= 11.105, p <.05). Performance in archery corelated significantly with the plank test after four weeks of the intervention. It is recommended that a core stabil ity training programme be incorporated into an archery training programme for adolescent archers.